Buku Fotografi Jamu Tradisional sebagai Media Promosi Produk Minuman Alternatif Hidup Sehat - Galuh Kumala Nifya (MAVIS : Jurnal Desain Komunikasi Visual, 2019)
Traditional herbal medicine is naturalingredients which made from nutritious plants to maintain health and cure diseases. It is still consumed by people currently because it is natural and not contain side effect. In the following time, life style of people start to change and medical is also more modern. The existence of traditional herbal medicine shifts especially among young people. Lack of people understanding about traditional herbal medicine, so it is needed visual communication media as informative media which consist of knowledge about traditional herbal medicine, the media is photography book. The design model beginning with writing of the background continued with data collection, there are primary data and secondary data, than data analysis, synthesis data, determine the design concept then make the design process to the final design. The method use in retrieving data is observation, documentation and interviews. This design product is photography book about traditional herbal medicine which the title is â€œSuwe Ora Njamuâ€ the content of this book will provide information about traditional herbal medicinethat history, utilization, traditional herbalist story in the present, recipe and efficacy ingredients used in traditional herbal medicine. The Information will be conveyed in a languange that easy to understand and interesting to read.